Propionate reinforces epithelial identity and reduces aggressiveness of lung carcinoma - Ramesh, Vignesh; Gollavilli, Paradesi Naidu; Pinna, Luisa; Siddiqui, Mohammad Aarif; Turtos, Adriana Martinez; Napoli, Francesca; Antonelli, Yasmin; Leal-Egaña, Aldo; Havelund, Jesper Foged; Jakobsen, Simon Toftholm; Boiteux, Elisa Le; Volante, Marco; et al. (Embo Molecular Medicine, 2023)
The epithelial-to-mesenchymal transition (EMT) plays a central role in the development of cancer metastasis and resistance to chemotherapy. However, its pharmacological treatment remains challenging. Here, we used an EMT-focused integrative functional genomic approach and identified an inverse association between short-chain fatty acids (propionate and butanoate) and EMT in non-small cell lung cancer (NSCLC) patients. Remarkably, treatment with propionate in vitro reinforced the epithelial transcriptional program promoting cell-to-cell contact and cell adhesion, while reducing the aggressive and chemo-resistant EMT phenotype in lung cancer cell lines. Propionate treatment also decreased the metastatic potential and limited lymph node spread in both nude mice and a genetic NSCLC mouse model. Further analysis revealed that chromatin remodeling through H3K27 acetylation (mediated by p300) is the mechanism underlying the shift toward an epithelial state upon propionate treatment. The results suggest that propionate administration has therapeutic potential in reducing NSCLC aggressiveness and warrants further clinical testing.
CRIS-Team Scopus Importer:2023-10-13
Keywords: epithelial–mesenchymal transition; H3K27 acetylation; metabolic inhibitor; metastasis; propionate